Diversity and biotechnological potential of rhizobia isolated from lima bean nodules collected at a semiarid region. Issue 5 (10th August 2021) - Louzada Rodrigues, Tainara; Martins da Costa, Elaine; de Almeida Ribeiro, Paula Rose; de Carvalho, Fernanda; Rufini, Márcia; Oliveira Silva, Aline; dos Santos Teixeira, Anita Fernanda; de Assis Pereira, Thiago; Reis Sales, Flávia; de Souza Moreira, Fatima Maria
Abstract: Lima bean ( Phaseolus lunatus L.) is the second most important species of the Phaseolus genus worldwide. In Brazil, it is grown primarily in the semiarid Northeast region. Although lima bean establishes symbiosis with N2 ‐fixing bacteria (rhizobia), there is not yet a recommended inoculant. The aim of this study was to phenotypically and genotypically characterize rhizobia strains isolated from root nodules of lima bean collected in a Northeast region, and to evaluate their efficiency in supplying N nutrition to the crop under axenic conditions and in a Humic Rhodic Hapludox with and without correction of acidity. The symbiotic efficiencies were evaluated in a greenhouse under axenic conditions and, afterward, in pots with nonautoclaved soil with and without liming. Treatments consisted of the strains under evaluation, controls without inoculation (with low or high concentration or without mineral N), and a strain efficient for the crop. In all, 66 strains were isolated from the root nodules with predominance of strains belonging to the Bradyrhizobium genus. Liming brought about increases in lima bean development as it interacted with some strains. Six strains of the Bradyrhizobium genus, belonging to groups of type strains that include B. elkanii and B. japonicum, stood out for their biotechnological potential as inoculants for lima bean, and they should be tested in the field with the aim of validating their recommendation as inoculants for that crop. Core Ideas: Lima bean establishes symbiosis mainly with Bradyrhizobium in a semiarid region. Liming did not affect the nodulation of lima bean by the efficient strains. Liming led to increases in the development of lima bean. Nodulation and N2 fixation by most of the strains were indifferent to liming. Many strains exhibit biotechnological potential as inoculants for lima bean.